A new approach for generating energy efficient discrete chirp signal of an UWB RFID reader circuit - Hossain, A. K. M. Zakir; Ibrahimy, Muhammad Ibn; Motakabber, S. M. A. (Penerbit UMT, Universiti Malaysia Terengganu (UMT), 2016)
The detection methodology for microstrip resonator type UWB RFID system relies on a constant and continuous chirp from the UWB RFID reader. It is difficult to generate a continuous linear chirp if the bandwidth goes up to 4 GHz. The entire UWB needs to be continuous swept to detect all the bits from an RFID tag. For the detection of a particular bit, only concerning frequency is needed. Consequently, the other frequencies are not being used. An electronic mixer is able to produce a lot of tones using two different frequencies. A desired frequency can be extracted by using a narrow band pass filter. Therefore, a number of required frequencies relevant with the tag can be generated by cascading mixer and filter circuits. The generation is only limited on those concerning frequencies allocated for the bits. As a result, the data from a tag is read without using a continuous frequency sweep in entire UWB. In addition, it is simple and energy efficient. A new approach has been proposed to design an RF front-end for the RFID reader circuit where the continuous chirp is not essential. The design is verified by using standard microwave simulation software. Four different frequencies from 5GHz to 5.6GHz in UWB each successively 200MHz apart are generated. The output power is observed around 7dBm for each frequency for a balanced load.